The Activity of the Neutral Sphingomyelinase Is Important in T Cell Recruitment and Directional Migration - Collenburg, Lena; Beyersdorf, Niklas; Wiese, Teresa; Arenz, Christoph; Saied, Essa M.; Becker-Flegler, Katrin Anne; Schneider-Schaulies, Sibylle; Avota, Elita (Frontiers in Immunology, 2017)
Breakdown of sphingomyelin as catalysed by the activity of sphingomyelinases profoundly affects biophysical properties of cellular membranes which is particularly important with regard to compartmentalisation of surface receptors and their signalling relay. As it is activated both upon TCR ligation and co-stimulation in a spatiotemporally controlled manner, the neutral sphingomyelinase (NSM) has proven to be important in T cell activation, where it appears to play a particularly important role in cytoskeletal reorganisation and cell polarisation. Because these are important parameters in directional T cell migration and motility in tissues, we analysed the role of the NSM in these processes. Pharmacological inhibition of NSM markedly interfered with early lymph node homing of T cells in vivo indicating that the enzyme impacts on endothelial adhesion, transendothelial migration, sensing of chemokine gradients or, at a cellular level, acquisition of a polarised phenotype. NSM inhibition reduced adhesion of T cells to TNF-α/IFN-γ activated, but not resting endothelial cells, most likely via inhibiting high-affinity LFA-1 clustering. It did not markedly affect transendothelial migration under inflammatory conditions, where ASM activity has been shown to be of importance. NSM activity proved to be highly important in directional T cell motility in response to SDF1-α, especially in confined environments. This showed in 3D migration experiments indicating that their ability to sense and translate chemokine gradients might be NSM dependent. In fact, pharmacological or genetic NSM ablation interfered with T cell polarisation both at an overall morphological level and redistribution of CXCR4 and pERM proteins on endothelial cells or fibronectin, as well as with F-actin polymerisation in response to SDF1-α stimulation, indicating that efficient directional perception and signalling relay depend on NSM activity. Altogether, these data support a central role of the NSM in T cell recruitment and migration both under homeostatic and inflamed conditions by regulating polarised redistribution of receptors and their coupling to the cytoskeleton.